2013
DOI: 10.1371/journal.pone.0060676
|View full text |Cite
|
Sign up to set email alerts
|

Tone Language Speakers and Musicians Share Enhanced Perceptual and Cognitive Abilities for Musical Pitch: Evidence for Bidirectionality between the Domains of Language and Music

Abstract: Psychophysiological evidence suggests that music and language are intimately coupled such that experience/training in one domain can influence processing required in the other domain. While the influence of music on language processing is now well-documented, evidence of language-to-music effects have yet to be firmly established. Here, using a cross-sectional design, we compared the performance of musicians to that of tone-language (Cantonese) speakers on tasks of auditory pitch acuity, music perception, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

35
264
4
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 256 publications
(307 citation statements)
references
References 83 publications
35
264
4
4
Order By: Relevance
“…In other words, the more difficult the musical pitch processing is, the more evident the advantage of tone language listeners possibly is. Our findings argue for a benefit of musical pitch processing as the result of growing up with a tonal native language, which is consistent with previous findings (Alexander et al, 2008;Bidelman et al, 2013;Pfordresher & Brown, 2009;Stevens et al, 2004;Wong et al, 2012;). Sensitivity to the pitch differences exhibited in the lexical tones is a prerequisite for acquiring them.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In other words, the more difficult the musical pitch processing is, the more evident the advantage of tone language listeners possibly is. Our findings argue for a benefit of musical pitch processing as the result of growing up with a tonal native language, which is consistent with previous findings (Alexander et al, 2008;Bidelman et al, 2013;Pfordresher & Brown, 2009;Stevens et al, 2004;Wong et al, 2012;). Sensitivity to the pitch differences exhibited in the lexical tones is a prerequisite for acquiring them.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings of improved accuracy in musical pitch processing among tone language listeners are consistent with previous studies (Alexander et al, 2008;Bidelman et al, 2013;Pfordresher & Brown, 2009;Stevens et al, 2004;Wong et al, 2012). The enhanced music perception is likely to be the result of growing up with a native tone language.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…19,20 Moreover, recent studies have shown that Cantonese speakers outperform their English-speaking non-musician counterparts on various measures of pitch and music perception. 21 Studies have demonstrated signifi cantly higher prevalence of AP among Asian students than their white counterparts, despite no difference in frequency of early music exposure. 7 Asian students, however, were signifi cantly more likely to have received 'fi xed-do' training than white students.…”
Section: Does It Matter?mentioning
confidence: 99%